The Supervisory Impact of School Principals on Instructional Excellence - Moses Adeleke Adeoye; Olaolu Paul Akinnubi; Oyeronke Christiana Paramole (Undiksha Press, 2023)
Instructional excellence is a key indicator of educational quality, heavily influenced by the leadership role of school principals. A recurring issue is the suboptimal implementation of instructional supervision, which hinders efforts to improve teaching and learning quality. This study aims to explore the impact of principal supervision on achieving instructional excellence within educational settings. A Systematic Literature Review method was employed, analyzing relevant theories and empirical findings drawn from scholarly databases such as Google Scholar, ResearchGate, SINTA, Scopus, and Web of Science. Data analysis was conducted using a thematic approach, focusing on core principles, behavioral theories, and instructional supervision strategies. The findings reveal that effective supervision plays a critical role in enhancing teaching practices, improving student learning outcomes, and fostering a positive school climate. Key factors influencing successful supervision include instructional leadership, communication skills, and collaborative engagement among principals, teachers, and other stakeholders. This review concludes that strengthening principals’ capacity for instructional supervision is a pressing need. The study implies that sustainable professional development programs are essential to empower school principals in cultivating high-quality and continuous learning environments.